Understanding and Predicting Post H-Atom Abstraction Selectivity through Reactive Mode Composition Factor Analysis - Maldonado-Domínguez, Mauricio; Srnec, Martin (Journal of the American Chemical Society, 2020)
The selective functionalization of C-H bonds is one of the Grails of synthetic chemistry. In this work, we demonstrate that the selectivity toward fast hydroxylation or radical diffusion (known as the OH-rebound and dissociation mechanisms) following H-atom abstraction (HAA) from a substrate C-H bond by high-valent iron-oxo oxidants is already encoded in the HAA step when the post-HAA barriers are much lower than the preceding one. By applying the reactive mode composition factor (RMCF) analysis, which quantifies the kinetic energy distribution (KED) at the reactive mode (RM) of transition states, we show that reactions following the OH-rebound coordinate concentrate the RM kinetic energy on the motion of the reacting oxygen atom and the nascent substrate radical, whereas reactions following the dissociation channel localize most of their kinetic energy in H-atom motion. These motion signatures serve to predict the post-HAA selectivity, and since KED is affected by the free energy of reaction and asynchronicity (factor η) of HAA, we show that bimolecular HAA reactions in solution that are electron transfer-driven and highly exergonic have the lowest fraction of KED on the transferred H-atom and the highest chance to follow rebound hydroxylation. Finally, the RMCF analysis predicts that the H/D primary kinetic isotope effect can serve as a probe for these mechanisms, as confirmed in virtually all reported examples in the literature.